Pengembangan Media Pembelajaran Berbasis Augmented Reality (AR) Berbantuan Aplikasi Assemblr Edu Pada Materi Bentuk Molekul - Fathoni Arif Pratama; Jeckson Siahaan; Nora Listantia (FKIP University of Mataram, 2025)
This study aims to determine the level of validity of the content and suitability of augmented reality (AR)-based learning media developed using the Assemblr Edu application for molecular structure material. This study employs the Design-Based Research (DBR) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, modified up to the development stage. Data collection techniques include interviews, validity questionnaires, and media feasibility questionnaires. Data validity analysis uses Aiken’s V formula, while media feasibility is measured using a percentage formula. The learning media product was tested on 28 eleventh-grade students at SMAN 1 Wanasaba. The validity test results showed that the media was highly valid with an Aiken’s V value of 0.92. The feasibility test results showed that the media was highly feasible with a percentage of 86.86%. This media is deemed valid and suitable for use as an innovative learning alternative to enhance students' understanding of molecular structure concepts. This study demonstrates that integrating AR technology into learning can serve as a strategic tool for optimizing the visualization of abstract concepts in a contextual, engaging, and relevant manner aligned with 21st-century needs.